2017
DOI: 10.1680/jmaen.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

Rock armour for birds and their prey: ecological enhancement of coastal engineering

Abstract: The authors present key design, construction and ecological enhancement criteria for sustainable coastal defence structures at Hartlepool, UK, a high-energy wave climate. Such 'ecologically favourable' coastal defences fulfil the habitats directive and key engineering and cost criteria. Bird, rocky intertidal ecological and biogeomorphological data underpin recommendations for 'passive' enhancement mitigation to maximise ecological potential involving rock armour material choice (partially enhanced) and its sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…As with foreshore structures, smooth surfaces, such as concrete, should be avoided as far as possible (Wiecek 2009;Firth et al 2014;Coombes et al 2015) or can be made rougher by casting irregular finishes (Wiecek 2009) or by chiselling grooves or drilling holes (Martins et al 2010;Nordstrom 2014;Hall et al 2018). Naylor et al (2017) showed how a rock revetment can be ecologically enhanced by informed selection and intentional positioning of armour rocks. Rock pools can be incorporated in seawalls to provide habitat for intertidal organisms by adding water-retaining features (Chapman and Blockley 2009;Firth et al 2016b;Chapman and Underwood 2011;Firth et al 2014).…”
Section: Adaptation Options For Seawallsmentioning
confidence: 99%
“…As with foreshore structures, smooth surfaces, such as concrete, should be avoided as far as possible (Wiecek 2009;Firth et al 2014;Coombes et al 2015) or can be made rougher by casting irregular finishes (Wiecek 2009) or by chiselling grooves or drilling holes (Martins et al 2010;Nordstrom 2014;Hall et al 2018). Naylor et al (2017) showed how a rock revetment can be ecologically enhanced by informed selection and intentional positioning of armour rocks. Rock pools can be incorporated in seawalls to provide habitat for intertidal organisms by adding water-retaining features (Chapman and Blockley 2009;Firth et al 2016b;Chapman and Underwood 2011;Firth et al 2014).…”
Section: Adaptation Options For Seawallsmentioning
confidence: 99%
“…Despite a wealth of proof-of-concept evidence, a clear policy pull and cross-sectoral support (all discussed in 1.2 and 1.3 above), there have been few examples of non-research-driven implementation of blue-green artificial structures in the UK (but see Naylor et al, 2017b), or indeed globally (but see Harris, 2003;Perkol-Finkel and Sella, 2016;Scyphers et al, 2015;Toft et al, 2013). So what are the barriers that remain?…”
Section: Barriers and Strategy Towards Blue-green Infrastructure In Tmentioning
confidence: 99%
“…We are beginning to see the start of a gradual shift from research-driven experimentation to practice-driven implementation. Naylor et al (2017b) report an example of practice-driven implementation of ecologically-sensitive design in a coastal defence scheme in the northeast of England. The implementation was driven by the local authority and regulators, who sought advice from the researchers.…”
Section: Barriers and Strategy Towards Blue-green Infrastructure In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The final paper by Naylor et al (2017) shows how relatively low cost changes to traditional hard engineering solutions can greatly enhance its biodiversity value. The work presents detailed ecological information to show how the proposed solution performed.…”
mentioning
confidence: 99%